2017
DOI: 10.17650/1726-9784-2017-16-4-74-79
|View full text |Cite
|
Sign up to set email alerts
|

Study of level and selectivity of liposomal form of photosensitiser hydroxyaluminium tetra-3-phenylthiophthalocyanine accumulation on transplantable mice tumor models at different ways of transplantation

Abstract: Background. Current work is devoted to the study in vivo of concentration and selectivity of accumulation of infrared photosensitizer (PS) hydroxyaluminium tetra-3-phenylthiophthalocyanine in liposomal form in intramuscularly and subcutaneously transplanted mice tumor models in comparison to normal tissues. Objective: to study the level and selectivity of accumulation of hydroxyaluminium tetra-3-phenylthiophthalocyanine liposomal form on mice tumor models in order to optimize the transplantation approach and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Before use, the contents of the vial are rehydrated with water for injection to obtain the recommended concentration 0.25 mg/ ml [3,4].…”
Section: Study Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Before use, the contents of the vial are rehydrated with water for injection to obtain the recommended concentration 0.25 mg/ ml [3,4].…”
Section: Study Medicationmentioning
confidence: 99%
“…In preclinical studies, it was found that Lipophtalocyan has a fairly high selectivity of accumulation in the tumor in relation to normal tissue due to encapsulation of PS in PEG liposomes. The advantages of this drug are high selectivity of exposure to tumor foci, low systemic toxicity, and high efficiency shown in vivo studies [3,4].…”
Section: Introductionmentioning
confidence: 99%